Pengaruh Fragmentasi Terhadap Digging Time Dan Produktivitas Excavator Liebher R9400 Pada Area Peledakan PT Dahana Site Adaro - Alex Lisendrik Nadapdap; Guskarnali Guskarnali; Haslen Oktarianty (MINERAL, 2020)
This research examines the effect of fragmentation on the digging time and productivity of the Liebher R9400 excavator at blasting area of PT Dahana site Adaro. The problem in this research is that the excavator productivity is not evenly distributed in each location, because the size of the fragmentation that is different in each location. The method used in this research is to analyze the factors supporting productivity such as digging time, efficiency and actual conditions in the field, and the method of image and obtained an average size of material fragmentation of 55.76 cm with the smallest fragmentation size of 29.15 cm and the largest size of 70.28 cm. the results based on actual obtained different productivity of excavators in research locations. The first productivity is 4,780.07 tons / hour with fragmentation of 53.1 cm, the second is 4,639,585 tons / hour with fragmentation of 62 cm, the third is 4,765,638 tons / hour with fragmentation of 56.14 cm, and the fourth is 4,746,547 tons / hour with 50.7 cm fragmentation. Based on the analysis it was concluded that the greater the size of the fragmentation, the productivity of the Liebher R9400 excavator will decrease and vice versa. However, there are several factors that affect excavator productivity, namely fragmentation quality, work efficiency, swing angle, tool maintenance, operator, swell factor, and digging ressistance.